On Invariant eigenvalues of Laplacian on complex star metric graphs - Soeharyadi, Yudi; Lindiarni, Janny; Agustima, Pilipus Neri; Burhan, Mohammad Januar Ismail (Hilbert Journal of Mathematical Analysis, 2023)
In this article eigenvalues of Laplacian acting on complex star metric graphs is considered. The operator is coupled with Neumann-Kirchhoff vertex condition, implying self adjointness of the operator. We exhibit the invariance of the eigenvalues over the number of the bonds of the star metric graphs. Moreover, the eigenvalues are also invariant over parallel bonds of the star metric multigraphs.